ANALISIS PELAKSANAAN PRAKTIKUM PADA PEMBELAJARAN BIOLOGI SISWA KELAS VIII DI SMP NEGERI 3 KUNTODARUSSALAM TAHUN PEMBELAJARAN 2014/2015 - Mariyam, Siti; Lestari, Rena; Afniyanti, Enny (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
This aim of this study was to known execution of practical work at study of class student biology of VIIIin SMP Country 3 Kunto Darussalam grade academic year 2014 / 2015. This was a descriptive study. Thesampel was the student of class VIIIA and class of VIIIB taken by simple random sampling till reach the amountof sampel as a whole 53 student. Technique intake of data done by using enquette. Data analyzed by usingdescriptive statistics. Result indicated that; 1) Frequency execution of practical work (75%); 2) Studententhusiasm to practical work (77%); 3) Time execution of practical work (69%) and; 4) Preparation andexecution of practical work (78%). Amount of mean percentage of execution of practical work at study ofbiology (75%) have been applied better.